Development of an Educational Program for Conflict Resolution Strategies Based on Olson’s Integrative Approach - Karimi, Marieh; Ghanbari Panah, Afsaneh; Hasani, Fariba (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to develop and evaluate an educational program based on Olson’s integrative approach to conflict resolution. Methods and Materials: The study followed a qualitative design, utilizing a research synthesis method to develop the program. A total of 30 documents related to conflict resolution strategies were reviewed, and an educational program was designed with 11 sessions. The content was evaluated using the Content Validity Ratio (CVR) and Content Validity Index (CVI). Ten experts in counseling and conflict resolution assessed the program through a five-point Likert scale questionnaire. Sessions that did not meet the minimum CVR of 0.62 were excluded from the final program. CVI was calculated for relevance, clarity, and practicality. Findings: Sessions related to communication, cohesion, and flexibility were rated highly, with CVR values between 0.80 and 1.0, indicating the content was essential and practical. Sessions one through six and eight through eleven were retained based on expert evaluations, while sessions seven and nine were removed for not meeting the minimum CVR requirement. The CVI results also indicated strong content validity, with most sessions scoring above 0.80 for clarity and relevance. The program was revised to include nine sessions, focusing on actionable conflict resolution strategies. Conclusion: The educational program developed using Olson’s integrative approach was validated as an effective tool for enhancing conflict resolution among couples experiencing emotional divorce. The findings underscore the importance of communication and emotional regulation strategies in managing relational conflicts. Further research is needed to assess the long-term impact of the program and explore alternative delivery methods.